Effects of Injection of Gamma-Aminobutyric Acid Agonists into the Nucleus Accumbens on Naloxone-Induced Morphine Withdrawal - YANANLI, HASAN RACİ (KARGER, 2017)
Aims: This study was to investigate the effects of local administration of gamma-aminobutyric acid (GABA) agonists into the nucleus accumbens (NAc) on naloxone-induced morphine withdrawal symptoms. Methods: Bilateral guide cannulas were stereotaxically implanted in the shell or core regions of the NAc of Sprague-Dawley rats. After a recovery period, 3 morphine pellets, each consisting of 75 mg morphine base, were placed subcutaneously on the first and third days of the study with the rats under mild ether anaesthesia. The GABA agonists, baclofen hydrochloride or muscimol hydrobromide, were injected into the NAc, and morphine withdrawal was induced by naloxone on the fifth day. Results: Administration of baclofen to the shell or core regions of the NAc of Sprague-Dawley rats led to statistically significant decreases in both behavioural and locomotor activity parameters during the morphine withdrawal period, compared to the control group. However, there were no statistically significant changes in locomotor activity or withdrawal behavioural parameters, with the exception of wet dog shakes, between control and muscimol-treated groups. Conclusion: These findings show that GABAergic conduction in the NAc is effective on the morphine withdrawal symptoms, and that both the shell and core regions of the NAc are associated with this effect. (C) 2017 S. Karger AG, Basel
Keywords: Gamma-aminobutyric acid; Nucleus accumbens; Sprague-Dawley rats; VENTRAL TEGMENTAL AREA; LOCUS-COERULEUS; DEPENDENT RATS; RECEPTOR AGONISTS; DOPAMINE RELEASE; GABA; OPIATE; SHELL; SIGNS; CORE